Divorce in Hong Kong SAR, 1999–2011: A Review of 1, 208 Family Court Cases. Issue 5 (4th July 2019) - Law, Yik-Wa; Chan, Melissa; Zhang, Huiping; Tai, Lianne; Tsang, Sandra; Chu, Patricia; Yip, Paul
ABSTRACT: Divorce has increased dramatically in Hong Kong and elsewhere in Asia since the 2000s, whereas the West has seen a decline, suggesting there are factors specific to Hong Kong relating to divorce. This study examined a random sample of 1, 208 divorce cases from the Hong Kong Family Court between 1999 and 2011. These marriages lasted 11 to 12 years on average, and most divorces occurred between the 5th and 7th years of marriage. Couples with a divorce history had a higher divorce risk, regardless of whether they had children, and predivorce marriage duration was positively associated with the number of children. The grounds cited for divorce indicate a shift toward no-fault divorce. Most petitioners were women, and mothers were generally granted child custody. Cross-border marriages and remarriages accounted for about one third of divorces, reflecting the impacts of differing sociocultural backgrounds and divorce history. The study's implications for policymaking and service provision are discussed.